(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Drashko O. М. The system of pedagogical conditions in training maintenance personnel teachers to use artistic handicrafts in a teaching and educational process. The article substantiates the system of pedagogical conditions in training maintenance personnel teachers to use artistic handicrafts. The author reveals criteria, indicators and levels of training specialists, stages of implementating the system of reasoned pedagogical conditions into a teaching and educational process of a university in regard to training maintenance personnel teachers to use artistic handicrafts in a teaching and educational process.